Pemanfaatan Google Lens sebagai Media Pembelajaran PPKN yang Efektif : Studi Kualitatif pada Siswa SMP Negeri 35 Medan Tahun Ajaran 2024/2025 - Dies L. Tobing; Abdinur Batubara (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to identify the implementation of Google Lens in PPKn learning at SMP Negeri 35 Medan, to see the effectiveness of using Google Lens in improving students' understanding of PPKn material, and to identify the obstacles faced in its use as a learning medium in the classroom. The main problem raised is the lack of student interest in PPKn learning, which is caused by the conventional teaching approach and the limited interaction of students with the material visually and contextually, so that the understanding of important concepts is less than optimal. This research method uses a qualitative approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) design. Data were collected through observation, interviews, and documentation. The results of the study indicate that Google Lens has been implemented in PPKn learning, making a positive contribution to increasing student interest and understanding through independent and interactive exploration of the material. However, several obstacles were found such as limited internet infrastructure and the need for teacher adaptation in integrating this technology optimally. Google Lens has proven effective in facilitating access to visual and contextual information, which has an impact on increasing student independence and understanding. The implications of this study highlight the potential of Google Lens as a valuable asset in education in the digital era and the need for infrastructure support and the development of innovative teaching strategies.